Development of PC based home energy management system - Muhamad Khairi, Che Yusoff (2007)
The usage of electrical power at home is something that always occurred in our life and it was a necessary to manage it in a systematic way to ensure the system operate in intelligent mode. In United State when users at home turn on the electrical appliances in peak time which contribute to the exceeding of limit power drop causing them to be charge in expensive rate. The purpose of this project is to design a control system at home to meet the objectives of monitoring the consumption’s rate of power, voltage level, current level, and turn on or off appliance through a computer. Methodology in implement this system could be categorized into software development and hardware design. The software develops based on graphical user interface in MATLAB 7.1 which is interface with hardware that used MC68HC11 as controller through serial communication. The hardware involves three stages which are signal conditioning circuit, controller and interfacing circuit. Operation of the hardware is started from signal conditioning circuit where voltage and current convert into voltage representation in range of 0V to 5V in order to fit the analog to digital converter (ADC) port at microcontroller. Voltage level of 240 Vrms need to be step down using voltage transformer and current measured by current transformer which is producing small voltage level and required amplification. Then microcontroller computes the power consumption and rms value of current and voltage and display at liquid crystal display (LCD). At the same time the microcontroller send the results of conversion of ADC to personel computer (PC) through serial communication. The application of organizing the energy could be seem when appliance also able to be control from GUI and also from external switch. Besides that, warning indicator at LCD exhibit when voltage and current level exceed certain limit and the limiting level could be determine from entering rms value at GUI. With the ability of manage of some certain characteristics of home’s electrical power supply it will produce a systematic system in organizing our energy.